Editor`s Foreword - Tolstykh N.N (Moscow State University of Psychology and Education, 2021)
A new issue of the journal "Psychological Science and Education" (No. 5-2021) is published. The main theme of this issue is learning motivation. Natalya Nikolaevna Tolstykh, PhD, became the invited thematic editor of the "Motivation and Interest in Learning" column. The studies presented in the column are devoted to academic motivation and self-motivation of educational activities; acquaints with modern methods of studying educational motivation; reveal the motivational preferences of students who are addicted to gadgets.